Thou shalt not: Religiosity and attitudes toward marijuana legalization. (December 2016) - Krystosek, Daniel James
Abstract: Substantial research supports the association between religiosity and the use of, or attitude toward, marijuana (Amoateng and Bahr 1986; Hastings and Hoge 1986; Hoffmann and Miller 1997; Steinman et al. 2008; Wallace et al. 2007). This study expands on past research by focusing on attitudes toward legalization, which has received little investigation in the extant literature (Trevino, 2002). Using the framework of social control theory, we examine variation in legalization attitudes by measures of religiosity and religious affiliation. Using three years (2006, 2008 and 2010) of General Social Survey (GSS) data, results partially support the hypothesis that greater religiosity reduces the likelihood of support for legalization. However, findings are also contrary to previous research; religious salience was not the strongest correlate of attitudes toward legalization. Theoretical, methodological, and policy implications are discussed.